Diagnostic utility of anti-thyroid peroxidase immunohistochemistry in the identification of papillary thyroid carcinoma - Suleman, Sahar; Fatima, Saira; Tariq, Muhammad Usman (Annals of diagnostic pathology, 2024)
The routine histomorphological assessment of follicular thyroid neoplasms has been subject to interobserver or intraobserver variability among histopathologists. Anti-thyroid peroxidase (anti-TPO) has emerged as a useful immunohistochemical (IHC) marker, with its expression lost in papillary thyroid carcinoma (PTC). Our study aims to determine the diagnostic accuracy of anti-TPO IHC expression in the identifying PTC and its variants, particularly the Follicular variant of papillary thyroid carcinoma (FVPTC), with H&E assessment as the gold standard. Anti-TPO IHC (DAKO-MoAb47) was performed on 110 cases, including 76 malignant tumors (classic PTC, FVPTC, follicular carcinoma (FC), and oncocytic carcinoma (OC)) and 34 benign tumors (non-invasive follicular tumor with papillary-like nuclear features (NIFTP) and follicular adenoma (FA)). The loss of expression in more than or equal to 51 % of thyrocytes was considered suggestive of a PTC profile. The sensitivity of the loss of anti-TPO expression for identifying PTC among all carcinomas was 61.7 %, specificity was 75 %, positive predictive value was 90.2 %, negative predictive value was 34.2 %, and accuracy was 64.4 %. The loss of anti-TPO IHC expression combined with routine H&E assessment, supports the identification of PTC and its variants. •Sensitivity of anti-TPO in lesions with papillary thyroid carcinoma like nuclei is 53.7 %, specificity is 100 %.•The positive predictive value is 91.7 %, negative predictive value is 38.7 % and accuracy is 61.8 %.•Sensitivity of loss of anti-TPO in papillary thyroid carcinoma, variants is 61.7 %, specificity is 75 %.•The positive predictive value is 90.2 %, negative predictive value is 34.2 % and accuracy is 64.4 %.•Anti-TPO is a useful stain, for follicular thyroid lesions with papillary thyroid carcinoma like nuclei.